Peran Pendidikan dalam Proses Peacebuilding di Sierra Leone - Ulfah Fatmala Rizky (The Indonesian Journal of Public Administration (IJPA), 2020)
Abstract, This paper intends to describe the conflict that occurred in Sierra Leone which resulted in the Complex Political Emergency (CPE) condition and the role of education in the peacebuilding process in Sierra Leone. This condition has reduced the Human Development Index in the country. In order to raise the Human Development Index in Sierra Leone, the conflict must end immediately. One of the ways to end the conflict is by doing peacebuilding. The peacebuilding process can be done through education. In addition, by increasing access to education or rebuilding the education system. The five roles of education in the peacebuilding process, namely: first, skills training that offers a new way of life apart from violence. Second, education protects children. Quality education will provide physical, psychosocial, and cognitive protection for children. Third, education helps rebuild 'normality' and self-confidence. Fourth, education helps restore social capital that has been lost and damaged by prolonged conflict. Fifth, education contributes to social transformation. Through the literature study method, this paper found that educational interventions in Sierra Leone have a positive impact on the peacebuilding process. Keywords: conflict, role of education, peacebuilding Abstrak, Tulisan ini bermaksud untuk menggambarkan konflik yang terjadi di Sierra Leone yang melahirkan kondisi Complex Political Emergencies (CPE) dan bagaimana peran pendidikan dalam proses peacebuilding di Sierra Leone. Di mana kondisi ini telah menurunkan Indeks Pembangunan Manusia di Negara tersebut. Untuk dapat meningkatkan Indeks Pembangunana Manusia di Sierra Leone maka konflik harus segera diakhir. Salah satu cara untuk mengakhiri konflik adalah dengan melakukan peacebuilding. Proses peacebuilding dapat dilakukan melalui pendidikan. Selain itu, dengan meningkatkan akses pendidikan atau membangun kembali sistem pendidikan. Lima peran pendidikan dalam proses peacebuilding, yaitu: pertama, pelatihan ketrampilan yang menawarkan jalan kehidupan baru selain kekerasan. Kedua, pendidikan melindungi anak-anak. kualitas pendidikan akan memberikan perlindungan fisikal, psikososial, dan juga kognitif bagi anak-anak. Ketiga, pendidikan membantu membangun kembali ‘normalitas’ dan kepercayaan diri. Keempat, pendidikan membantu untuk memperbaiki modal sosial yang hilang dan rusak akibat konflik yang berkepanjangan. Kelima, pendidikan berkontribusi pada transformasi sosial. Melalui metode studi kepustakaan, tulisan ini menemukan bahwa intervensi pendidikan di Sierra Leone memberikan dampak positif terhadap proses peacebuilding. Kata kunci: konflik, peran pendidikan, pembangunan perdamaian